Meta-analysis unravels common responses of seed oil fatty acids to temperature for a wide set of genotypes of different plant species - Alberio, Constanza; Aguirrezábal, Luis A. N. (Frontiers in Plant Science, 2024)
Temperature is the main environmental determinant of seed oil fatty acid Q9 composition. There are no models describing common responses of main seed oil fatty acids to temperature in plants. The aim of thus work was to investigate common responses of seed oil fatty acids to minimum temperature during grain filling across species and genotypes. A database consisted of 164 genotypes of 9 species, sunflower, rapeseed, soybean, maize, flax, chia, safflower, olive and camelia, grown under a wide range of environmental conditions, was created and analyzed applying meta phenomics tools. Four widely sown species of the database was used to develop several common seed fatty acid responses and validate some models, and the other species were used to validate the General Model. The minimum temperature during grain filling responses of fatty acids in the General Model were close to responses found in genotypes of five independent species used to validate the model. Dissections of the general model by selecting the appropriate data allowed unraveling previously unknown features of the response of fatty acid to the minimum temperature during grain filling. The response of fatty acids to temperature for any species was unaffected by experimental conditions (field or controlled conditions) during the oil synthesis stage. The oleic acid trait did not affect the response to temperature of fatty acids synthesized downstream and upstream of it. Traits such as high stearic or high linoleic did not affect the response of fatty acids synthesized upstream or downstream of the trait. The established models and new knowledge could be applied to design cost effective and timely experiments to assess the potential responses of seed oil fatty acids to temperature of previously untested genotypes.